Regulation of CD44 expression in human monocytic cells and B cells - Mishra, Jyoti Prasad (University of Ottawa (Canada), 2008)
CD44, a family of cell adhesion glycoproteins, is an important mediator in events such as tumorigenesis and metastasis, cell migration, and inflammatory responses. The molecular mechanisms in the regulation of CD44 expression are not well understood. In this study, I examined the regulation of CD44 expression in two models systems: human monocytic cells and Burkitt's lymphoma B cells. Lipopolysaccharide (LPS), a bacterial cell wall component, regulates CD44 expression, and modulates CD44-mediated biological effects in monocytic cells during inflammation and immune responses. In human monocytic cells, LPS and the proinflammatory cytokine, tumor necrosis factor-alpha (TNF-alpha) are potent inducers of CD44 expression. To delineate the mechanism underlying LPS- and TNF-alpha-induced CD44 expression, the previous results in our laboratory showed the differential role of mitogen-activated protein kinase (MAPK) specifically c-Jun N-terminal kinase (JNK) in LPS-induced but not in TNF-alpha-induced CD44 expression. Therefore, we hypothesized that distinct signaling pathways are involved in the regulation of CD44 expression in a stimulus and cell-dependent manner. In this study, I investigated the signaling pathway involved in TNF-alpha-induced CD44 expression in human monocytic cells. I used human promonocytic THP-1 cells, transfected stably with CD14 receptor (THP-1/CD14) as a model system. My results showed the differential involvement of Ca2+ signaling molecules, in particular calmodulin (CaM) and CaM-dependent protein kinase-II (CaMK-II), in TNF-alpha-induced but not in LPS-induced CD44 expression. The CD44 promoter analysis suggests that the distinct transcription factors AP-1 and Egr-1 may be involved in TNF-alpha- and LPS-induced CD44 expression, respectively. In addition, I demonstrated the selective involvement of Ca 2+ signaling molecules, mainly CaM and CaMK-II, in TNF-alpha-induced CD44 expression through the activation of transcription factor AP-1. In contrast, LPS-induced CD44 expression was regulated by JNK MAPK through the activation of Egr-1. I have also demonstrated that phosphoinositide 3-kinase (PI3K) constitutes a key downstream component of both the signaling pathways involved in the regulation of LPS- and TNF-alpha-induced CD44 expression in human monocytic cells. My results suggest that the JNK-activated PI3K regulates LPS-induced CD44 expression through the activation of Egr-1, whereas TNF-alpha induces CD44 expression by a distinct CaM/CaMK-II-activated PI3K through the activation of AP-1 transcription factor. Further, to determine the involvement of the subunit of PI3K, I demonstrated that the regulatory subunit p85alpha is involved in both LPS- and TNF-alpha-induced CD44 expression, without involving the catalytic subunit, p110alpha. IL-4, a pleotropic cytokine, has been shown to enhance the survival and development of Burkitt's lymphoma (BL) B cells, and induces the expression of various costimulatory molecules including CD44. In addition, CD44 induction and its ability to bind hyaluronan (HA) have been suggested to play a vital role in in vivo BL tumor growth and dissemination. However, the role of IL-4 in the pathogenesis of BL and other B cell malignancies is not clear. In this study, I investigated the regulation of IL-4-induced CD44 expression in an Epstein-Barr virus (EBV)-transformed Burkitt's lymphoma B cell line, BL30/B95-8 cells. The results suggested that IL-4 did not induce the expression of the transcription factors Egr-1 and AP-1. However, IL-4 induced STAT-6 which plays a critical role in CD44 regulation in these cells. I demonstrated that STAT-6 is activated by two distinct signaling pathways namely Jak-1/3 and ERK MAPK and independent of the IRS-2/PI3K pathway. Therefore, STAT-6 and ERK MAPK may represent an important and novel target for regulation of CD44 expression and CD44-mediated immune responses in B cell proliferation- and maturation-related disease conditions and cancer malignancies. Further, my results also suggest a critical involvement of PI3K in the regulation of LPS- and TNF-alpha-induced CD44 expression in human monocytic cells, and hence, may represent a potential therapeutic target for inhibiting CD44 expression and consequent CD44-mediated cell migration, inflammation and autoimmune disorders.
Keywords: Biology, Microbiology.